Retrospective Investigation of The Association Between the Length of Dry Period and Lactation Milk Production and Lifetime Traits During the Subsequent Lactations - EL-Hedainy, Dalia K.; Ramadan, Ramadan M.E.; Saleh, Ahmed A.; Sharaby, Mahmoud A.; Rashad, Amr M.A. (Journal of Advanced Veterinary Research, 2023)
A total of 5844 normal lactation records on 1483 Holstein-Friesian cows were collected from El-Alamiah dairy farm in Egypt through the period from 1996 to 2018 to study the effect of the length of dry period on the subsequent lactation performance by evaluating the performance of milk production traits, lifetime traits and some welfare factors of Holstein-Friesian cows, raised in Egypt, to determine the best length of dry period. The milk production traits studied were total milk yield (TMY, kg), 305 days milk yield (305-d MY, kg) and lactation length (LL, day). The lifetime performance traits under study were complete lactation number (CLN, no.), productive life length (PL, month), longevity length (Lon, month), lifetime total milk yield (LTY, kg) and lifetime daily milk yield (LDY, kg). Welfare factors studied were mastitis and lameness scores. Â TMY, 305 d-MY and LL tended to increase with increasing DP length up to 90 d then decreased thereafter. While the lowest TMY and 305 d-MY (6470.76 and 5435.25 kg, respectively) and the shortest LL (305.81 d) were obtained when DP was below 31. Cows had DP category of 61 to 75d produced the largest amount of milk (34506.39 kg) in a longest Lon and PL (90.56 and 62.65 mo., respectively) and attained the biggest number of CLN (4.474 lactations). All lifetime traits tended to increase with increasing DP up to 61 to 75d then decreased thereafter. The 61 to 75 d DP had the largest mastitis number (0.3532), while DP category of 76 to 90d was associated with the highest lameness number (0.7976). However, no trends were observed in these traits with different DP length categories. The correlation coefficients between DP and all productive traits were significantly negative and ranged between -0.064 to -0.038. DP had no significant correlations with the health traits. Generally, the dry period of 61-75 days is the most optimum for Holstein Cows raised under subtropical warm climate. However, more studies to confirm these results under the Egyptian conditions are required.